Ozone and UV radiation - Bernhard, G. H.; Fioletov, V. E.; Grooß, J.-U.; Ialongo, I.; Johnsen, B.; Lakkala, K.; Manney, G. L.; Müller, R.; Svendby, T. (American Meteorological Society, 2023)
Past emissions of manufactured chlorine-containing substances such as chlorofluorocarbons (CFCs) have caused substantial chemical depletion of stratospheric ozone (WMO 2022). The resulting ozone loss led to increases of ultraviolet (UV) radiation at Earth’s surface with adverse effects on human health and the environment (Barnes et al. 2019; EEAP 2023). The chemical destruction of polar ozone occurs within a cold stratospheric cyclone known as the polar vortex, which forms over the North Pole every year during winter (WMO 2022). The 2022 polar vortex was somewhat colder than usual; between late January and March 2022, minimum temperatures in the vortex near 16 km–20 km altitude were about 1 st. dev. below the 2005–21 average.